Gender Mainstreaming In Rural Development Planning - Fatmariza, Fatmariza; Suasti, Yurni; Fitria Dewi, Susi (Opción, 2019)
This article aims to analyse the implementation of Gender Mainstreaming (GM) in rural development planning. This research was conducted in one vil- lage in West Sumatra using a qualitative approach. The results of this study indicate that development planning in the village has not reflected the resolu- tion of the problems related to gender issues. Development programs written in the Village Medium Term Development Plan (RPJM) have not yet inte- grated gender issues. Women’s empowerment is a separate program from the other programs. This happens because the village development planners do not have a good knowledge and understanding of gender mainstreaming. Pro- gram planning is not based on gender issues because the village does not have gender-disaggregated data for the various aspects of community development in the village. The values that develop in the community do not fully support the women’s participation in development planning.